Library of Congress Copyright Office Mask Work deposits - Library of Congress. Copyright Office
A representative sampling of mask works (schematic plans or layouts of an integrated circuit or computer chip) deposited with the Library of Congress Copyright Office.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Per the Semiconductor Chip Protection Act of 1984, mask works are deposited with the Copyright Office by their manufacturers. The Copyright Office is obligated to retain the designs for thirteen years after registration. Because Copyright Records Management was ready to dispose of the mask works it was no longer obligated to keep, the Manuscript Division decided to retain them by transfer. The Manuscript Division retained a representative sampling (every twentieth deposit).
Keywords: Integrated circuit layout; Integrated circuits -- Design and construction